Comparative Studies of Phytophthora Palmivora from Cocoa and Durian and Their Control - Chan, Luz G. (1985)
Phytophthora palmivora (But 1.) Butler is known to be a variable or ganism and is considered to be one of the most destructive pathogens of cocoa and durian which are being inter cropped in Malaysia. Studies were under taken to compare the cultural characteristics, sexuality, and pathogenicity of six Phytophthora isolates from these crops as well as the in-vitro and in-vivo efficacy of fungicide s against the pathogen. Preliminary studies on the use of a bio-control agent against the organism were also looked into. Cultural studies established that the Phytophthora isolates belonged to MFI P. palmivora. They produced stellate and striate colonies on carrot, cornmeal, and V-8 juice agar media. Mycelial growth was opt imum at 28 + 1.5C. No growth occurred at 36C. Sporangia were caducous, with length: breadth ratios from 1.22 to 1.8 and possessed short, occluded pedicels. Abundant chlamydospores were produced in culture.